Hydroxide and oxide of germanium(IV): synthesis and chemical-physical properties - E. E. Nikisihina; E. N. Lebedeva; A. V. Piletsky; D. V. Drobot (Тонкие химические технологии, 2015)
Our work is focused on a development of physical-chemical backgrounds and methods of controlled synthesis of germanium hydroxide GeO(OH)2, which is a precursor for the synthesis of functional materials based on germanium oxide. The method of controlled synthesis of germanium hydroxide by heterophase interaction ammonia solution with germanium tetraiodide was elaborated. It yields hydroxide with relatively low water content (~ 14 wt. %), which can be easily filtrated. The average germanium dioxide content is as higher as 86 wt.%. Physical-chemical properties of germanium hydroxide and products of thermal decomposition have been investigated by using of chemical and thermal analysis, gravimetric analysis, XRDA, IR-spectroscopy.